2017
DOI: 10.1111/cpr.12383
|View full text |Cite
|
Sign up to set email alerts
|

Low‐intensity pulsed ultrasound activates ERK1/2 and PI3K‐Akt signalling pathways and promotes the proliferation of human amnion‐derived mesenchymal stem cells

Abstract: Low-intensity pulsed ultrasound can promote the proliferation of hAD-MSCs, and ERK1/2 and PI3K-Akt signalling pathways may play important roles in this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 65 publications
6
79
0
Order By: Relevance
“…The PI3K/AKt pathway plays an important role in cell growth, survival, proliferation, and cell cycle progression. Previous studies have confirmed that PI3K/AKt has an important role in the proliferation and differentiation of MSCs . Cell cycle progression relies on cyclins and cyclin‐dependent kinase (CDK) .…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKt pathway plays an important role in cell growth, survival, proliferation, and cell cycle progression. Previous studies have confirmed that PI3K/AKt has an important role in the proliferation and differentiation of MSCs . Cell cycle progression relies on cyclins and cyclin‐dependent kinase (CDK) .…”
Section: Discussionmentioning
confidence: 99%
“…The same nanoconstruct was studied to deliver oxygen to hypoxic tissues, exploiting the boiling point of the perfluoropentane core (32°C). In fact, whereas this compound is liquid at room temperature, it is in vapour phase at body temperature, leading [155][156][157][158][159][160][161][162][163][164][165][166][167][168][169][170][171][172] to an higher expansion of the nanobubbles and enhancing the release of loaded oxygen molecules under ultrasound irradiation [102]. In addition to liposomes and polymeric NPs, also metallic and inorganic nanoconstructs could represent efficient platforms for carrying sonosensitizer molecules.…”
Section: Nps Used In the Sonodynamic Therapymentioning
confidence: 99%
“…Chemical Engineering Journal 340 (2018) [155][156][157][158][159][160][161][162][163][164][165][166][167][168][169][170][171][172] residual air bubbles inside the silicon nanoporous structure and by the formation of gas (hydrogen) bubbles due to silicon NPs' dissolution [110]. Nevertheless, concerning the class of NPs employed as nanosensitizers in SDT, the most widely studied are titanium dioxide (TiO 2 ) NPs.…”
Section: G Canavese Et Almentioning
confidence: 99%
See 2 more Smart Citations